2019
DOI: 10.1080/16549716.2018.1559496
|View full text |Cite
|
Sign up to set email alerts
|

Socio-anthropological methods to study the feasibility and acceptability of the minimally invasive autopsy from the perspective of local communities: lessons learnt from a large multi-centre study

Abstract: The minimally invasive autopsy (MIA), an innovative approach for obtaining post-mortem samples of key organs, is increasingly being recognized as a robust methodology for cause of death (CoD) investigation, albeit so far limited to pilot studies and research projects. A better understanding of the real causes of death in middle- and low-income countries, where underlying causes of death are seldom determined, would allow improved health planning, more targeted prioritization of available resources and the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
9
0
2
Order By: Relevance
“…The key factors like no mutilation, disfigurement, organ retrieval, and disrespect to the body were considered positive for MITS compared to the CDA. These observations were similar to the reports from Muslim and Christian dominated communities [ 29 , 31 , 33 , 34 , 38 ]. Timing of death appeared to influence MITS acceptance as the burial should be completed before end of the day [ 33 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…The key factors like no mutilation, disfigurement, organ retrieval, and disrespect to the body were considered positive for MITS compared to the CDA. These observations were similar to the reports from Muslim and Christian dominated communities [ 29 , 31 , 33 , 34 , 38 ]. Timing of death appeared to influence MITS acceptance as the burial should be completed before end of the day [ 33 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Anticipated acceptability variables derived from a secondary analysis of data from the ethnographic component of the CaDMIA study on local attitudes and perceptions related to death and willingness to know the cause of death described in detail elsewhere [ 15 , 40 ]. From September 2013 to April 2015, deaths in the previous 1–30 days within or outside the health facilities (HF) were notified by HF staff, DHSS field workers, or community informants to social behavioural sciences (SBS) research team members, who then invited the closest relative present at the time of death to a one-on-one semi-structured interview.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothetical acceptability of MITS has also recently been assessed across diverse geographic settings, including north India [ 3 ], Kenya [ 6 ], Mali [ 6 ], Mozambique [ 6 ], Pakistan [ 5 ], and the United Kingdom [ 7 ]. These studies have demonstrated a high theoretical acceptability of MITS across a range of participants, including parents, relatives of the deceased, healthcare providers, and religious and community leaders [ 3 , 5 7 ].…”
Section: Introductionmentioning
confidence: 99%